Exploring the Sustainability of Education in Jamaica: Trends, Insights and Future Implications - Komala, E. (Journal of Research in Vocational Education, 2025)
This research study examines sustainable development trends within Jamaica's education sector focusing on educators' and students' perceptions of sustainable practices. Utilising a mixed-methods approach, data were collected from 20 educators and 40 students across Kingston, St. Andrew, and St. Catherine. The instruments used for this study including questionnaires, focus group discussions and interviews to gather quantitative and qualitative data, over a three month-period. The findings provided valuable insights into the current trends prevailing in sustainable development, which are integration into curriculum, experiential learning approaches, teacher training and professional development, interdisciplinary collaboration, and community engagement. Additionally, 82% of the students and 100% of the educators shared that they believed that sustainable practices in education is very important inside and outside the classroom. Findings revealed that while awareness of sustainable development is generally positive, significant gaps exist in educators' preparedness to these concepts. The study underscores the need for enhanced professional development and more integrated sustainability initiatives within the curriculum to better equip both educators and students for future challenges.